Removal of free fatty acid in Palm Fatty Acid Distillate using sulfonated carbon catalyst derived from biomass wastefor biodiesel production. Issue 1 (January 2016) - Hidayat, Arif; Rochmadi,; Wijaya, Karna; Budiman, Arief
Abstract: In this research, the esterification of PFAD using the sulfonatedcoconut shell biochar catalyst was studied. Carbon solid catalysts were prepared by a sulfonation of carbonized coconut shells. The performances of the catalysts were evaluated in terms of the reaction temperatures, the molar ratios of methanol to PFAD, the catalyst loading and the reaction times. The reusability of the solid acid carbon catalysts was also studied in this work. The results indicated that the FFA conversion was significantly increased with increasing catalyst loading and reaction times. It can be concluded that the optimal conditions were an PFAD to methanol molar ratio of 1:12, the amount of catalyst of 10%w, and reaction temperature of 60 o C.At this optimum condition, the conversion to biodieselreached 88%.